The results of treatment of femoral diaphysis fractures using locked intramedullary osteosynthesis and extramedullary osteosynthesis (results for 10 years) - V. G. Fedorov; I. V. Kuzin (Acta Biomedica Scientifica)
Background. Femoral diaphysis fractures are one of the most common and significant injuries to the bones of the limbs. Locked intramedullary osteosynthesis makes it possible to reduce the injury rate of the surgery and its length, as well as to carry out early rehabilitation of patients. The aim of the study. To conduct a continuous retrospective single-purpose comparative study of  the results of treatment of patients with femoral diaphysis fractures treated with locked intramedullary osteosynthesis and extramedullary osteosynthesis for 10 years. This study did not include patients with double femoral fractures treated by osteosynthesis using a combination of two implants – locked intramedullary implant and extramedullary implant. Material and methods. We conducted a retrospective study of the results of treatment of patients from 2011 to 2020. During this period, we treated 794 patients aged from 16 to 77 years with femoral diaphysis fractures. The share of people of working age was 75 %. The patients were divided into two groups depending on the method of surgical treatment. Group 1 included 500 patients who had surgical treatment using locked intramedullary osteosynthesis. Group 2 included 294 patients who had surgical treatment using extramedullary osteosynthesis. Results. In patients of group 1 treated with locked intramedullary osteosynthesis, good anatomical and functional treatment results were achieved in 70 % of cases; satisfactory treatment results – in 25.2 % of cases, unsatisfactory results – in 4.8 %. In the group 2, good results were achieved in 61.9 % of cases, satisfactory – in 29.6 %, unsatisfactory – in 8.5 %. Conclusion. The obtained results of treatment of femoral diaphysis fractures show the undeniable advantage of using locked intramedullary osteosynthesis compared to extramedullary osteosynthesis.